Fault Ride-Through Capability Enhancement for Microinverter Applications - Arab Ansari, Sajad; Mizani, Amir Reza; Ashouri, Siamak; Shokrollahi Moghani, Javad (Journal of Renewable Energy, 2019)
Due to the fast growth of single-phase grid-connected photovoltaic (PV) systems, the existing grid codes are expected to be modified to guarantee the availability, quality, and reliability of the electrical system. Therefore, the future single-phase PV systems should become smarter and support low voltage ride-through (LVRT) capability, which are required for three-phase wind power systems. In this paper, the operation principle of a flyback inverter in a low-voltage ride-through operation is demonstrated in order to map future challenges. The steady state performance of the flyback inverter under voltage rise and drop conditions at boundary conduction mode (BCM) and discontinues conduction mode (DCM) is studied theoretically. The simulation results of the flyback inverter for various grid faults are presented to verify the theoretical analyses. The results indicate the fact that the flyback inverter at BCM condition can provide LVRT capability for photovoltaic microinverter applications in distributed generation (DG) systems, even though it does not need any auxiliary control branches and any limitations in components design.